(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Women in rural areas are catalysts for the social, economic, & environmental change that is necessary for society’s long-term viability. For rural communities to progress and women to feel empowered, it is essential that they actively participate in politics. The battle against marginalisation, trivialisation & oppression, as well as the socio-economic growth of rural women, depend on their political engagement and empowerment. Cultural norms, education, economic independence, & government policies are some of the aspects that have been studied as potential facilitators or deterrents to political activity among rural women. Additionally, it evaluates the broader social effects of their involvement, including advancements in gender equality, stronger government, and enhanced social welfare. In this research, we will represent that a positive association between women’s labour force participation and GDP growth. A more diverse and inclusive district may see faster development and progress if more women are involved in the political process, have high-quality leadership roles, and have decision-making authority.